Programmatic implementation of depression screening and remote mental health support sessions for persons recently diagnosed with TB in Lima, Peru during the COVID-19 pandemic - Contreras, Carmen (2024)
Background: Few studies have explored a stepped care model for delivering mental health care to persons with tuberculosis (TB). Here, we evaluated depression screening and remote low-intensity mental health interventions for persons initiating TB treatment in Lima, Peru during the COVID-19 pandemic. Methods: We used the Patient Health Questionnaire 9 (PHQ-9) to screen participants for depressive symptoms (PHQ-9 ≥ 5). Participants with PHQ-9, 5–14 received remote Psychological First Aid (PFA) or Problem Management Plus (PM+). Participants were reevaluated 6 months after intervention completion. We then compared the change in median PHQ-9 scores before and after intervention completion. Those with PHQ-9 ≥ 15 were referred to higher-level care. Findings: We found that 62 (45.9%) of the 135 participants had PHQ-9 ≥ 5 at baseline. Then, 54 individuals with PHQ-9, 5–9 received PFA, of which 44 (81.5%) were reevaluated. We observed significant reductions in median PHQ-9 scores from 6 to 2 (r = 0.98; p < 0.001). Four participants with PHQ-9, 10–14 received PM+ but were unable to be reevaluated. Four participants with PHQ-9 ≥ 15 were referred to higher-level care. Conclusions: Depressive symptoms were common among persons recently diagnosed with TB. We observed improvements in depressive symptoms 6 months later for most participants who received remote sessions of PFA.